Are All Children Equal? Causative Factors of Child Labour in Selected Districts of South Punjab, Pakistan - Syed Zubair Haider; Ayesha Qureshi (Springer, 2016)
The present study investigates the causative factors of child labour in selected districts of South Punjab, Pakistan. As member of the International Labour Organization (ILO) Pakistan has a responsibility to stamp out child labour from its regions. Our sample was selected from seven working environments (workshops, hotels, tea stalls, households, etc.) through purposive sampling. The data were collected via a questionnaire which was completed by a sample of 547 working children. The ﬁndings of the exploratory factor analysis (EFA) explored four factors from the research. Multilevel analyses were calculated to pinpoint the causative factors of child labour. The study results revealed that, due to family responsibilities, a lack of educational opportunities for children from low-income families, and increasing poverty, children develop an interest in working to earn their livelihood at the cost of their education. The children are involved in labour because their parents cannot meet their personal and educational requirements.